1979
DOI: 10.1051/rnd:19790924
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of the viability of early bovine embryos by fluorescence microscopy

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 5 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Evaluation of the staining response of embryos while immersed in dye has been reported (Brock andRowson 1950, Hutz et al 1985). However, most methods for embryonic assessment using dyes require or recommend that the embryo is washed prior to evaluation of the staining response (Church and Raines 1980, Hoppe and Bavister 1984, Kardymowicz 1972, Mohr and Trounson 1980, Schilling et al 1979, Thadani et al 1982. Of those studies, only a few (Mohr andTrounson 1980, Thadani et al 1982) exposed the embryo to the dye in the same medium used to culture the embryo and then determined the staining response, after washing…”
Section: Effects Of Thermal Shock On Embryonic Development and The Stmentioning
confidence: 99%
See 4 more Smart Citations
“…Evaluation of the staining response of embryos while immersed in dye has been reported (Brock andRowson 1950, Hutz et al 1985). However, most methods for embryonic assessment using dyes require or recommend that the embryo is washed prior to evaluation of the staining response (Church and Raines 1980, Hoppe and Bavister 1984, Kardymowicz 1972, Mohr and Trounson 1980, Schilling et al 1979, Thadani et al 1982. Of those studies, only a few (Mohr andTrounson 1980, Thadani et al 1982) exposed the embryo to the dye in the same medium used to culture the embryo and then determined the staining response, after washing…”
Section: Effects Of Thermal Shock On Embryonic Development and The Stmentioning
confidence: 99%
“…Mohr and Trounson (1980) noted that the amount and rate of fluorescein accumulation varied greatly within embryos or even between embryos at the same stage of development. However, none of the studies so far reported has specifically Investigated for an influence of the stage of embryonic development on the staining response (Church and Raines 1980, Hoppe and Bavlster 1984, Hutz et al 1985, Mohr and Trounson 1980, Schilling et al 1979). …”
Section: Effects Of Thermal Shock On Embryonic Development and The Stmentioning
confidence: 99%
See 3 more Smart Citations